English Teachers’ Roles on Mobile-Assisted Language Learning-Based Strategies during Emergency Remote Teaching in 11th Grade of SMK Negeri 1 Denpasar - Rasmiani, Desak Made Sutra; Made Hery Santosa; Gede Mahendrayana (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
This study aims to determine the roles of teachers and the problems found when using MALL-based strategies in SMK Negeri 1 Denpasar during Emergency Remote Teaching. This study is a mixed-method design. The respondents were 8 English teachers. There are three instruments used in this study namely, questionnaires, observation sheet and interview guide. The results of validity show 1.00 while the results of reliability showed .874. Quantitative data analysis used descriptive statistical analysis and qualitative data were used interactive model analysis. The results of the questionnaire refer to Very True of Me and True of Me, meanwhile the results of the observations identified that 7 of 8 teachers had been practiced this role. In interview session with the teachers the problems found are 1) as a facilitator, not all of the students can answer well in quiz, 2) as a resource developer, many students think English is a difficult subject, 3) as a counselor, many students did not attend the online classes, 4) as a manager/organizer, lack motivation in learning, 5) as a participant, teacher does not take part in discussions and 6) as a controller, have not been able to control all of students activities in using MALL. Further, teaching by technology can be applied continuously for future learning, either for full or as blended learning.